Out of Pocket Expenditure in Patients on Maintenance Hemodialysis: A Single Center Study - Agrawaal, Krishna Kumar; Shah, Santosh (Nepalese Medical Journal, 2022)
Introduction: The government of Nepal has been providing free dialysis for a lifetime to its citizen since 2016. Most of the patients have to spend from pocket to meet their medical demands to sustain life. This leads to a financial burden and may lead to the sale of the property. The aim of this was study to look into different categories of expenses done by patients in the Bipanna nagarik free HD program provided by the government of Nepal. Materials and Methods: This descriptive cross-sectional study was carried out from 9th February 2022 till 30th September 2022 under the Nephrology Unit, Department of Internal Medicine at Universal College of Medical Sciences, Bhairahawa, Nepal. Ethical clearance was taken from the Institutional Review Committee (IRC letter reference no. UCMS/IRC/049/22). Patients receiving free basic hemodialysis services under the Bippana Nagarik Scheme of the Government of Nepal and giving informed and written consent were enrolled in the study. Non-Probability Sampling Method – Convenience Sampling was done. Results: In our study of 50 patients on HD, the mean age was 46.24 ± 15.31 years. The mean duration of dialysis of the study population was 126.80 ± 332.52 months. The average family income per annum was approximately NRs. 31000. The total out-of-pocket expenditure was approximately NRs. 35305/month. The cost of blood investigations was approximately NRs. 13000 in three months. Conclusion: The monthly out of pocket expenditure was approximately NRs. 35000 which was directly related to hemodialysis in spite of free basic hemodialysis services by the Government of Nepal.